Impact of N-substitution on structural, electronic, optical, and vibrational properties of a thiophene–phenylene co-oligomer. Issue 47 (27th July 2020) - Trukhanov, Vasiliy A.; Dominskiy, Dmitry I.; Parashchuk, Olga D.; Feldman, Elizaveta V.; Surin, Nikolay M.; Svidchenko, Evgeniya A.; Skorotetcky, Maxim S.; Borshchev, Oleg V.; Paraschuk, Dmitry Yu.; Sosorev, Andrey Yu.
Abstract : Properties of the organic semiconductors can be finely tuned via changes in their molecular structure. Abstract : Properties of the organic semiconductors can be finely tuned via changes in their molecular structure. However, the relationship between the molecular structure, molecular packing, and (opto)electronic properties of the organic semiconductors to guide their smart design remains elusive. In this study, we address computationally and experimentally the impact of subtle modification of a thiophene–phenylene co-oligomer CF3 -PTTP-CF3 on the molecular properties, crystal structure, charge transport, and optoelectronic properties. This modification consists in the substitution of two C–H atom pairs by N atoms in the thiophene units and hence converting them to thiazole units. A dramatic effect of the N-substitution on the crystal structure—the crossover from the herringbone packing motif to π-stacking—is attributed to significant changes in the molecular electrostatic potential. The changes in the molecular and crystal structure resulting from the N-substitution clearly reveal themselves in the Raman spectra. The increase of the calculated electron mobility in the corresponding crystals as a result of the N-substitution is rationalized in terms of the changes in the molecular and crystal structure. The charge transport, electroluminescence, and photoelectric properties are compared in thin-film organic field-effect transistors based on CF3 -PTTP-CF3 and its N-substituted counterpart. An intriguing similarity between the effects of N-substitution in the thiophene rings and fluorination of the thiophene–phenylene oligomer is revealed, which is probably associated with a more general effect of electronegative substitution. The obtained results are anticipated to facilitate the rational design of organic semiconductors.